2015
DOI: 10.1521/jscp.2015.34.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Negative Inferences as Mediators of the Predictive Association Between Early Maladaptive Schemas and Depressive Symptoms in Adolescents

Abstract: The present study examined an etiological model of depressive symptoms in adolescents, through which the predictive relationships between early maladaptive schemas (young, 1999) and depressive symptoms were hypothesized to be mediated by negative inferences made about stressors (abramson, Metalsky, & alloy, 1989). More specifically, this study tested a chain in which interpersonal schemas indirectly affect depressive symptoms through negative social inferences, and autonomy schemas indirectly affect depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…For example, in a longitudinal study with a sample of university students in Canada, endorsing more severe EMSs (e.g., abuse, defectiveness, and failure) predicted greater depression over time [ 13 ]. Consistent with findings in adults, these same relationships existed in studies conducted with adolescents [ 14 16 ].…”
Section: Introductionsupporting
confidence: 86%
“…For example, in a longitudinal study with a sample of university students in Canada, endorsing more severe EMSs (e.g., abuse, defectiveness, and failure) predicted greater depression over time [ 13 ]. Consistent with findings in adults, these same relationships existed in studies conducted with adolescents [ 14 16 ].…”
Section: Introductionsupporting
confidence: 86%
“…Moreover, evidence of external locus of control, social distress, depressive symptoms, low self-confidence and self-esteem, negative school perception, difficult parental relationships, personal maladjustment (with tendency to shyness), and severe emotional distress has been reported in children exposed to IPV (Brown, Fite, Stone, & Bortolato, 2016;Mateos-Pérez, Calvete, & Hankin, 2015;Seijo, Fariña, Corrás, Novo, & Arce, 2016). As regards external locus of control and sense of self-efficacy, some authors have concluded that children exposed to inter-parental conflict perceived high levels of threat and coping inefficacy and were at greater risk of internalizing disorders (Camisaca, Miragoli, Blasio, & Grych, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no instrument that can be used in Spanish-speaking countries to evaluate women's traditional gender beliefs from a REBT perspective. This is important because studies in Spain have shown that dysfunctional cognitive schemas are related to psychological symptons [ 49 , 50 ]. In addition, studies have shown the importance of cognitive representations in the genesis and maintenance of gender-based violence [ 69 ], as well as in the predisposition to develop psychological disorders such as depression and stress in adolescents [ 1 ].…”
Section: Introductionmentioning
confidence: 99%